A cross-sectional study of pesticide use and knowledge of smallholder potato farmers in Uganda - Okonya, J.; Kroschel, Jürgen (Hindawi Limited, 2015)
This study sought to promote proper and safe pesticide-handling practices by providing data needed to guide pesticide regulation policy and training for extension staff and farmers. A household survey was conducted in three major potato-growing agroecological zones of Uganda. Two hundred and four potato farmers were interviewed about the type and source of pesticides they use in potato cultivation, the frequency of applications, the use of protective clothing, and cases of pesticide poisoning.